Mencermati Implementasi Whole of Government: - Astuti Azis (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
Bureaucratic reform appears to be the central agenda for good governance. One crucial strategy to achive it is implementing whole of government. Several provinces and regencies in Indonesia had tried to implement the policy. Jogjakarta, Denpasar, Surabaya, and Pontianak are good references for the program. This study reports best practices of the implementation of whole of government through a sysytematic review. The result of the review shows that the key success for the program implementation covers strict approach by regulation, the availabilibity of sufficient fund to run the program and strong collaboration and integration of all relevant sectors in order to achieve the vision of the government. Recommendation on how similar study should be conducted in the future also suggested at the end of the review.